Cognitive and Non-Cognitive Skills, Hiring Channels, and Wages in Bangladesh - Anne Hilger; Christophe Jalil Nordman; Leopold Sarr (Institute of Labor Economics (IZA), 2018)
This paper uses a novel matched employer-employee data set representing the formal sector in Bangladesh to provide descriptive evidence of both the relative importance of cognitive and non-cognitive skills in this part of the labor market and the interplay between skills and hiring channels in determining wages. While cognitive skills (literacy, a learning outcome) affect wages only by enabling workers to use formal hiring channels, they have no additional wage return. Non-cognitive skills, on the other hand, do not affect hiring channels, but they do enjoy a positive wage return. This wage return differs by hiring channel: those hired through formal channels benefit from higher returns to openness to experience, but lower returns to conscientiousness and hostile attribution bias. Those hired through networks enjoy higher wages for higher levels of emotional stability, but they are also punished for higher hostile attribution bias. This is in line with different occupational levels being hired predominantly through one channel or the other. We provide suggestive evidence that employers might use hiring channels differently, depending on what skill they deem important: employers valuing communication skills, a skill that could arguably be observed during selection interviews, are associated with a larger within-firm wage gap between formal and network hires, while the importance of teamwork, a skill that is more difficult to observe at the hiring stage, is associated with a smaller wage gap.
Keywords: J24; J31; J71; O12; 330; cognitive skills; personality traits; networks; matched worker-firm data; Bangladesh